Management of pericoronitis associated with tooth 48 using operculectomy - Andi Supriatna; Alia Fatimah Maulani; Syifa Madila Ridwan Abdullah (PT WIM Solusi Prima, 2026)
Pericoronitis of the mandibular third molar is often associated with gingival tissue that partially covers the tooth crown, leading to trauma and food impaction. This case report aims to describe the management of pericoronitis of tooth 48 through operculectomy in a 25-year-old female patient who presented at the Achmad Yani General Dental and Oral Hospital. The patient presented with complaints of swelling in the lower right posterior gum, food frequently getting trapped in the gum tissue covering the tooth, and the gum being bitten frequently while eating. Data were obtained through medical history, intraoral and extraoral clinical examinations, and panoramic radiography. Clinical examination revealed that gingival tissue partially covered the tooth crown, while radiographic examination showed a Class I position of the right mandibular third molar with adequate eruption space. Management was carried out through Phase I therapy consisting of oral hygiene education and scaling, followed by Phase II therapy consisting of an operculectomy as a conservative treatment. Evaluations were conducted at one-week and one-month follow-ups, as well as periodic maintenance visits every three months. The treatment results showed no reports of pain, good tissue healing, and a reduction in complaints of food getting stuck. Operulectomy can be a conservative treatment option for pericoronitis involving a mandibular third molar with adequate eruption space to alleviate the patient’s symptoms and eliminate local causative factors, thereby supporting the possibility of continued eruption, while still requiring periodic monitoring and evaluation to prevent recurrence.